Lycopene supplementation: effects on oxidative stress, sex hormones, gonads and thyroid tissue in tilapia Oreochromis niloticus during Harness® exposure - Ismail, Rania F.; Hamed, Mohamed; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2023)
Harness® is a commercial herbicide that contains acetochlor (ACET) at a concentration of 84% as an active ingredient. Ubiquitous, persistent, and substantial uses of Harness® in agricultural processes have resulted in pollution of nearby water sources, posing a danger to various aquatic biotas, including fish. The effects of Harness® toxicity on fish health are little known. So, this study aimed to describe the impact of Herbicide Harness® on the oxidative stress, reproductive and thyroid performance of male and female tilapia (Oreochromes niloticus), and also to investigate the prospective role of the natural antioxidant lycopene (Lyc) supplementation in dismissing Harness® (Ha) adverse properties. Antioxidant enzymes (CAT, SOD and TAC), Hormones measurements (T, E2, T3 and T4) were detected, and gonadal and thyroid follicles histological sections were examined as a method to investigate the effects of Harness® toxicity on fish. Male and female tilapia were exposed to (10 μmol /L and 100 μmol/L of Harness®) and treated with 10 mg Lycopene/kg for 15 days of exposure. Our results demonstrated that the antioxidants enzyme activity was altered by (Ha) exposure, and serum T for both males and females were dropped, also female E2 level decreased, but male E2 upsurges. Harness® higher dose exposure induced elevation in both T3 and T4 levels, although the low exposure dose stimulated T4 level. Harness® exposure prompted histological variations and degenerative changes in testicular, ovarian, and thyroid follicles tissues. Lycopene supplement administration diminished oxidative stress induced by Harness®, alleviated its endocrine disparaging effects by neutralizing T3, T4, T and E2 and ameliorating the histological structure of gonadal and thyroid tissues. In conclusion, Lycopene supplementation preformed to normalize the alterations and oxidative damage caused by Harness® in Nile tilapia, suggesting that lycopene supplemented diet functioned as potent antioxidants and able to alleviate oxidative stress, thyroid and reproductive toxicity caused by herbicide Harness®. Moreover, it is crucial to take appropriate care when consuming herbicides to defend the aquatic environment.